Pengaruh Profitabilitas, Likuiditas, Sales Growth, dan Struktur Aset terhadap Struktur Modal: Studi Empiris pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2019 - 2023 - Mutiara Baramukti; Desy Mariani (Jurnal Riset Akuntansi, 2024)
This study aims to determine the effect to profitability, liquidity, sales growth, and asset structure on capital structure in food and beverage sector companies listed on the Indonesia Stock Exchange for the 2019 – 2023 period of 95 companies. The data used in this study were obtained from financial statement data and annual reports. The population in this study are food and beverage sector companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling method and obtained 215 sample data from 43 companies. The analysis technique used in this study is multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) version 22. The results of this study indicate that profitability, liquidity, and asset structure have a negative and significant effect on capital structure, while sales growth has no effect on capital structure.